If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-z+6)+2=-18
We move all terms to the left:
3(-z+6)+2-(-18)=0
We add all the numbers together, and all the variables
3(-1z+6)+2-(-18)=0
We add all the numbers together, and all the variables
3(-1z+6)+20=0
We multiply parentheses
-3z+18+20=0
We add all the numbers together, and all the variables
-3z+38=0
We move all terms containing z to the left, all other terms to the right
-3z=-38
z=-38/-3
z=12+2/3
| 3a2+11a-4=0 | | 4x+5+6x-2=24 | | -4=r.20-5 | | 10m+3=12+8m | | (x+3)*(x+4)=(x+1)*(x+2) | | -25-7m=6(4m+1) | | 31=-7n | | -4/p=12 | | 1/3=1/4+f | | 2x2+9=-41 | | .5^z=1.3 | | 63=x+3x+5x | | 5/9y+26=-6 | | 9/5+3/5x=31/15+8/3x+1/3 | | 11(b+7)=40 | | -2=2+v.25 | | 39/x=35/100 | | (x-1)*(x+7)=(x+1)*(x-3) | | -34=-61-9f | | 6(2+6r)-6=-66 | | b-(-16)=0 | | 7(2x+4+3x)=10 | | 8/x+1=4/7 | | 10/x=20/100 | | x+5/12=1/6 | | 7+1=5x+9+7 | | -4(1+8n)+1=-2n-33 | | x+8/3=11/3 | | 9x+7-4x=2x+19 | | 105+9.5e=14.75 | | z=72-82/8 | | -4(1+8n)+1=-2-33 |